Recent Advances in Quinoline-Based Macrocycles: Synthesis, Properties, and Applications in Catalytic Reactions - Xu, Wei; Kumagai, Naoya (Synthesis, 2024)
Macrocyclic compounds exhibit unique properties due to their large ring-shaped structures, which have captivated chemists in recent decades. These molecules exert specific functions in various applicable fields, such as chemistry, materials science, and biology. Crown ethers, calixarenes, and porphyrinoids, which contain several ether/phenol/pyrrole subunits, represent these molecular categories with unparalleled functional diversity. In contrast, quinoline-based macrocycles comprising the quinoline unit as a key element to construct specific ring shapes have received limited attention. In this minireview, we summarize the recent advances in oligoquinoline macrocycles TriQuinoline (TQ), oxa-TriQuinoline (o-TQ), TEtraQuinoline (TEQ), and other bridged quinoline-based macrocycles. Emphasis is placed on the synthesis, structure, and application of these molecules in organometallic and supramolecular chemistry, which may guide new molecular designs in the quinoline-based macrocycle family.1 Introduction2 Quinoline-Based Macrocycles2.1 TriQuinoline (TQ)2.2 Oxa-TriQuinoline (o-TQ)2.3 TEtraQuinoline (TEQ)2.4 Larger Quinoline-Based Macrocycles with Bridges3 Conclusion
Keywords: quinoline; TriQuinoline; oxa-TriQuinoline; TEtraQuinoline; quinoline-based macrocycles